DSM-5 Posttraumatic Stress Disorder Symptoms in Nonclinical Samples of Chinese and Pakistani Trauma-Exposed Adults: Factor Structure and Invariance Across Culture. Issue 6 (28th June 2022) - Liu, Xu; Wang, Li; Hussain, Sadiq; Fang, Ruojiao; Cao, Chengqi; Elhai, Jon D.
Abstract: The purpose of the current study was to examine the latent structure and cross-cultural measurement validity of the Diagnostic and Statistical Manual of Mental Disorders ( DSM-5 ) posttraumatic stress disorder (PTSD) symptoms assessed by the PTSD Checklist for DSM-5 . Participants comprised trauma-exposed Chinese and Pakistani undergraduate students ( N = 495 and N = 186, respectively). Confirmatory factor analysis (CFA) indicated that a seven-factor hybrid model involving intrusion, avoidance, negative affect, anhedonia, externalizing behaviors, anxious arousal, and dysphoric arousal factors provided good fit in both samples. This model fit significantly better than three alternative models including the DSM-5 four-factor model and six-factor anhedonia and externalizing behaviors models. The subsequent multigroup CFA showed that the best-fitting hybrid model demonstrated cross-cultural measurement invariance. Our findings provide further empirical support for the seven-factor PTSD hybrid model and its cross-cultural invariance, and have implications for understanding and application of DSM-5 's PTSD symptoms.